(untitled) - Francis Essien; Charles Jacocks; Matthew Carroll (SAGE Publishing, 2022)
Celiac disease (CD) is a multisystem disorder known to manifest in a multitude of ways to include diarrhea, anemia, and nutritional deficiencies. The malabsorptive state can present as certain classical conditions such as autoimmune gastritis and osteopenia/osteoporosis but scurvy is less recognized within the literature. In this case, we present a unique presentation of scurvy as a result of an undiagnosed CD.